Production of porous copper with high surface area for efficient water purification. (May 2016) - Michailidis, Nikolaos; Stergioudi, Fani; Seventekidis, Panagiotis; Tsouknidas, Alexander; Sagris, Dimitrios
Abstract: Porous copper of controllable and uniform pore distribution was produced by a space holder technique, yielding to an attractive combination of properties like high surface area, ductility and thermal conductivity, rendering favourable its use in industrial applications such as filters, fuel cells and heat exchangers. The pore characteristics (size, shape and porosity) defining the surface area, as well as the surface integrity of the cells were defined by micro computed tomography and profilometry. The mechanical properties of porous copper was determined by uniaxial compression, while their high efficiency in purifying water were correlated with porosity (wetting surface) characteristics.